Malala Yousafzai: Telaah Perjuangan Feminisme dalam Menanggulangi Patriarki dan Kesenjangan Gender di Pakistan Tahun 2009–2012 - Avicenna Al Maududdy; Septian Fatianda (Medan Resource Center, 2026)
Malala Yousafzai’s advocacy for girls’ education in Pakistan emerged within a socio-political context marked by entrenched patriarchy and systemic restrictions on women’s access to education. This study investigates how Malala’s struggle constitutes a form of feminist resistance against gender inequality and examines the extent to which her advocacy reshapes discourses and policies concerning women’s rights. Employing a qualitative approach with a literature-based research method, the study analyzes Malala’s speeches, writings, and institutional initiatives, particularly through the Malala Fund, to assess their social, political, and educational impact. The findings demonstrate that Malala’s activism not only amplified global awareness of girls’ education as a fundamental human right but also contributed to policy advocacy for more inclusive educational frameworks in Pakistan and beyond. Her movement challenges patriarchal norms by positioning education as a transformative instrument of empowerment and collective agency. The study argues that Malala’s feminist engagement illustrates how education functions as a strategic pathway to dismantle structural patriarchy and foster more equitable social change.